Analysis of Productivity and Costs of Heavy Equipment in Road & Drainage Work on The Marvel - 3 Unilever Oleochemical Indonesia Project - Lazuardin Nukman Lubis; Kartono Wibowo; Abdul Rochim (Jurnal Planologi, 2026)
Heavy equipment productivity is a critical determinant of time and cost performance in road and drainage construction projects, particularly in industrial environments where operational restrictions may affect equipment efficiency. This study evaluates the productivity of heavy equipment used in road and drainage works at the Modern Cikande Industrial Estate, Banten, Indonesia, including excavators, dump trucks, motor graders, vibratory rollers, and foco trucks. The analysis combines field-measured cycle times, productivity calculations based on national standards, fleet balance analysis, and operating cost estimation. The results show that excavators, motor graders, vibratory rollers, and foco trucks achieved productivity levels close to or exceeding standard benchmarks, while dump truck productivity declined significantly due to speed restrictions imposed for safety reasons within the industrial area. The analysis identifies an optimal equipment configuration of one excavator and seven dump trucks, generating effective productivity of 27.23 m³/hour with an operating cost of IDR 3,265,205 per hour. The novelty of this study lies in its context-specific decision-support framework that integrates field productivity, safety constraints, equipment balance, and operational cost under restricted industrial operating conditions. The findings contribute practical guidance for contractors and project managers in improving fleet allocation and cost efficiency while maintaining compliance with industrial safety regulations.Keywords: heavy equipment productivity; fleet balancing; industrial construction; equipment management; operational efficiency; drainage construction.  Produktivitas alat berat merupakan faktor penentu yang krusial terhadap kinerja waktu dan biaya pada proyek konstruksi jalan dan drainase, khususnya di lingkungan industri yang memiliki pembatasan operasional yang dapat memengaruhi efisiensi alat. Penelitian ini mengevaluasi produktivitas alat berat yang digunakan pada pekerjaan jalan dan drainase di Kawasan Industri Modern Cikande, Banten, Indonesia, meliputi excavator, dump truck, motor grader, vibratory roller, dan foco truck. Analisis dilakukan dengan mengombinasikan pengukuran waktu siklus lapangan, perhitungan produktivitas berdasarkan standar nasional, analisis keseimbangan armada, serta estimasi biaya operasional. Hasil penelitian menunjukkan bahwa excavator, motor grader, vibratory roller, dan foco truck mencapai tingkat produktivitas yang mendekati atau melampaui standar acuan, sedangkan produktivitas dump truck mengalami penurunan signifikan akibat pembatasan kecepatan yang diterapkan untuk alasan keselamatan di kawasan industri. Analisis mengidentifikasi konfigurasi alat yang optimal, yaitu satu excavator dan tujuh dump truck, yang menghasilkan produktivitas efektif sebesar 27,23 m³/jam dengan biaya operasional sebesar Rp3.265.205 per jam. Kebaruan penelitian ini terletak pada kerangka pendukung keputusan yang spesifik terhadap konteks, yang mengintegrasikan produktivitas lapangan, kendala keselamatan, keseimbangan alat, dan biaya operasional dalam kondisi operasional industri yang terbatas. Temuan penelitian ini memberikan panduan praktis bagi kontraktor dan manajer proyek dalam meningkatkan alokasi armada dan efisiensi biaya, dengan tetap memenuhi ketentuan keselamatan di kawasan industri.Kata kunci: produktivitas alat berat; keseimbangan armada; konstruksi industri; manajemen peralatan; efisiensi operasional; konstruksi drainase.